The Impact of Physical Activity and Social Support on Cognitive Ability and Motor Skills of Students - Heru Tamam; Dedi Supriadi; Vicki Ahmad Karisman (Universitas Negeri Semarang, 2026)
Physical inactivity among adolescents is a growing public health concern that may negatively affect cognitive and motor development. In Indonesia, many children and adolescents do not meet recommended physical activity levels, a situation worsened by sedentary lifestyles and increased screen time. This study aims to analyze the impact of physical activity and social support on the cognitive ability and motor skills of students. The studi uses a quantitative approach with a descriptive quantitative method and an associative causal design (ex post facto). Using the stratified random sample technique, 60 students from Senior High School Bhayangkari Bandung participated in the study. Physical activity was measured using the Physical Activity Questionnaire for Adolescents (PAQ-A), social support was measured using the Social Support Scale for Exercise Behavior, cognitive ability was measured using the General Cognitive Assessment Battery (GCAB) based on a computer, and motor skills were measured using the Motorische Basiskompetenzen (MOBAK) level 2 instrument. Data were analyzed using descriptive statistics and multiple linear regression analysis. The research results show that physical activity has a positive and significant impact on cognitive and motor skills, and is the most dominant factor compared to social support. Social support also has a positive and significant impact on cognitive and motor skills, although its contribution is smaller compared to physical activity. Simultaneously, physical activity and social support significantly influence cognitive and motor skills, indicating that both factors contribute together to support the development of learners. Adequate physical activity and social support are important factors that need to be considered in efforts to improve students' cognitive and motor skills.